Pengaruh Wawasan Kevokasionalan Siswa SMP di Kecamatan Selong Terhadap Minat Melanjutkan di SMK - Fathoni, Ahmad; Ismatulloh, Kholida (Fakultas Teknik Universitas Negeri Malang, 2020)
This research aimed to describe (1) how much vocationalization insight that junior high school students had on vocational high school as a working world education (X1), understanding the types of skills (X2), and understanding of the working world (X3) on the interest to continue to vocational high school (Y); (2) how much is the vocationalization insight influence in junior high school students year IX comprised of vocational high school as a working world education (X1), understanding the types of skills (X2), and understanding of the working world (X3) on the interest to continue to vocational high school (Y). This research was survey research using a quantitative approach. The samples were 197 students that were determined using a proportionate random sampling technique. The sample size determination referred to the Isaac & Michael table with 5 percent error rate. The data collection used questionnaire, document, and observation. The data were analyzed using descriptive statistic. The results showed that (1) X1, X2, and X3 variables entered the high category with the percentage values of 60 percent, 57 percent, and 51.2 percent or good variables for the interest to continue to vocational high school; (2) the X1, X2, X3 variables influenced the Y variable with the correlation coefficient of 0.580, 0.564, and 0.479 respectively, and together, X1, X2, and X3 variables influenced the Y variable with the correlation coefficient of 0.727.